Analisis Kebutuhan Pengguna dalam Meningkatkan Kualitas Pelayanan Ruang Baca Departemen Teknik Sipil Fakultas Teknik Universitas Andalas - Yulinda, Azra; Hidayat, Benny; Mulya, Ayu Marta; Syukria, Alfi (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2025)
Background of the Study: Reading rooms serve as essential facilities that support academic learning and research in higher education. However, increasing user needs have revealed potential gaps in the quality of services provided. At the Department of Civil Engineering, Universitas Andalas, several students reported discomfort and limited access to certain services, which may reduce the effectiveness of the reading room as a learning support space Objectives: This study aimed to evaluate the service quality of the reading room by combining the SERVQUAL model and Maslow's hierarchy of needs to assess how well the services meet user expectations and fundamental the needs. Method: The research employs a descriptive quantitative method by distributing questionnaires to 100 active students from the Civil Engineering Department who have visited the library. The SERVQUAL model, which includes five dimensions—Reliability, Responsiveness, Assurance, Empathy, and Tangibles—was used to assess the service quality. Additionally, Maslow’s Hierarchy of Needs theory was applied to evaluate the fulfillment of users' needs based on physiological, safety, social, esteem, and self-actualization dimensions. The data obtained was analyzed using descriptive quantitative analysis. Finding: The findings revealed significant service gaps in the dimensions of tangibles and responsiveness. Many students expressed dissatisfaction with physical comfort, digital access, and staff support. In terms of user needs, the study found that basic physiological and safety needs were not fully met, which affected higher-level needs such as esteem and self-actualization. Conclusion: The study concludes that improving physical facilities, enhancing digital resources, and increasing staff responsiveness are critical to elevating the service quality of the reading room. These improvements are expected to better fulfill students’ learning needs and contribute positively to their academic experience.